Peran Pendekatan Sistem dalam Meningkatkan Kualitas Pembelajaran - Hasyim Basid; Zahra Nabila Iqbal; Eka Satya; Abdul Fatah Nasution (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
The systems approach is an effective framework for improving the quality of learning across various levels of education. In the context of education, this approach emphasizes the importance of interaction among various components, such as curriculum, teaching methods, resources, and the learning environment. This study aims to explore the role of the systems approach in identifying problems, designing appropriate interventions, and evaluating learning outcomes. By employing the systems approach, educators can better understand the dynamics within the learning process and optimize each element to achieve better educational outcomes. The study results indicate that the implementation of the systems approach not only enhances student engagement but also fosters collaboration between educators and other stakeholders. Therefore, the systems approach serves as a crucial tool in educational reform efforts to create more effective and sustainable learning environments.